BURDEN OF CANCER ATTRIBUTABLE TO SMOKING IN GULF COOPERATION COUNCIL (GCC) COUNTRIES, 2015 - Mouaddh Abdulmalik; Montarat Thavorncharoensap (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Smoking is a major cause of premature mortality worldwide. Smoking is recognized as the leading preventable cause of cancer and mortality from cancer. This study aims at estimating the number of cancer mortality and years of potential life lost (YPLL) attributable to smoking in GCC countries in 2015. Methods: Smoking prevalence was combined with Relative Risks (RRs) of cancer to obtain smoking attributable fractions (SAFs). Mortality data of people older than 15 years were derived from WHO deaths estimates while life expectation was obtained from WHO life tables 2015. Sixteen types of cancer were included in the analysis. Results: Smoking is responsible for 2,141 cancer deaths among people aged 15 years and above in GCC countries (1,895 deaths among men, 246 deaths among women). This represents 15% of cancer deaths in GCC (26.43% in male, 3.5% in female). Additionally, cancer deaths attributable to smoking were responsible for 40,485 YPLL (35,361 years among men, 5,124 years among women). Conclusion: Smoking causes a considerable burden in GCC countries in term of mortality and years of potential life lost. Effective smoking control initiatives and sustained efforts are needed to minimize cancer burden in the future.